Graphene quantum material and preparation method thereof
By using technical means such as molten salt catalysis and high-temperature treatment in the preparation of graphene quantum materials, the problems of low yield, uneven particle size distribution and insufficient purity and uniformity in the existing technology are solved, and the preparation of high purity, uniform particle size distribution and versatile graphene quantum films are achieved.
Patent Information
- Application Number
- CN202411808277.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
The existing preparation methods of graphene quantum materials have problems such as low yield, uneven particle size distribution, and insufficient product purity and uniformity.
Graphene quantum materials are prepared by using molten salt catalysis and high-temperature treatment steps, through mechanical mixing, preheating treatment, high-temperature treatment, cooling and immersion, centrifugation and dialysis, drying and collection, surface treatment and functional treatment.
The high purity and uniform particle size distribution of graphene quantum dots are achieved, and the average particle size is controlled below 3 nanometers. The obtained graphene quantum film has high temperature resistance, acid and alkali resistance, and waterproof properties, ensuring the safety and long-term stability of the product.
Smart Images

Figure CN119706818A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene quantum material preparation, and in particular to a graphene quantum material and a preparation method thereof. Background Art
[0002] With the development of nanotechnology, two-dimensional materials, especially graphene, have attracted widespread attention due to their unique physical and chemical properties. Graphene is a single-layer carbon atom in the form of sp 2 The two-dimensional structure composed of hybrid orbitals has excellent electrical conductivity, thermal conductivity and mechanical strength.
[0003] At present, there are many methods for preparing graphene quantum dots, including hydrothermal method, electrochemical method, microwave-assisted method, etc. These methods have their own advantages and disadvantages, but the common problems are low yield and uneven particle size distribution.
[0004] After searching, the application scheme of Chinese patent application number CN202111149446.7 discloses a technology and device for preparing graphene quantum materials by ultrashort pulse laser induced cracking, which mainly uses ultrashort pulse laser resonance to excite the vibration mode of organic molecules in biomass carbon-containing precursor materials with high energy, so that the corresponding chemical bonds therein are broken, and the carbon-containing precursor materials are cracked and recombined into bonds to prepare graphene quantum materials. The technology in the above patent has the following shortcomings: the prepared products are still insufficient in purity and uniformity. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a graphene quantum material and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a graphene quantum material comprises the following steps:
[0008] S1: Material collection: mechanically mix graphite powder blocks and molten salt catalyst in a mass ratio of 1:3-7 to obtain a mixture;
[0009] S2: Pretreatment: preheat the mixture of S1 at 320-480°C and keep it warm for 0.8-1.8 hours to remove impurities in the mixture;
[0010] S3: High temperature treatment: directly heat the preheated mixture to 580-680℃ and keep it warm for 1.2-2.2 hours;
[0011] S4: Cooling and soaking: After the mixture treated at high temperature is cooled to room temperature, it is treated with deionized water and ultrasonically separated for 1.2 hours to obtain a suspension;
[0012] S5: Centrifugation and dialysis: Centrifuge the suspension at 11,000 rpm for 25-35 minutes to remove the residual starting material; dialyze the centrifuged liquid for 1.5-2.5 days using a dialysis bag with a molecular weight cutoff of 600-900 Daltons, changing the water every 12 hours;
[0013] S6: Drying and collection: The dialyzed product is vacuum dried at 65-75°C for 18-26 hours to obtain a finished graphene quantum dot product;
[0014] S7: Surface treatment: The surface of the finished graphene quantum dot product is treated with a polymer resin; the polymer resin uses epoxy resin and polyvinyl alcohol, and the treatment method includes dipping and spraying to obtain a graphene quantum film;
[0015] S8: Functionalization treatment: immerse the graphene quantum film in an amino or carboxyl solution for 2-4 hours; take it out and dry it at 60-70°C for 12-24 hours.
[0016] Preferably: in S1, the specific steps of taking materials are:
[0017] S11: Graphite powder block selection: Select industrial-grade graphite powder blocks, ensuring that the ash content is no more than 0.05%, the moisture content is no more than 0.02%, the carbon content is more than 99%, and the particle size is 800-12000 mesh;
[0018] S12: Preparation of molten salt catalyst: select cesium carbonate molten salt as a catalyst and mix them in a mass ratio of 1:4; put the cesium carbonate molten salt into a drying oven and preheat it to 100° C. to remove moisture;
[0019] S13: Mechanical mixing: Put the graphite powder block and the preheated cesium carbonate molten salt into a ball mill and mix them at a speed of 300 rpm for 2 hours.
[0020] Preferably: in S2, the specific steps of pre-processing are:
[0021] S21: Preheating treatment: preheat the mixture of S1 at 360°C and keep it warm for 1 hour; use a high temperature furnace for preheating;
[0022] S22: Impurity removal: Protected by inert gas to prevent oxidation; use a vacuum system to remove volatile impurities;
[0023] S23: Cooling: Cool naturally to room temperature and set aside.
[0024] Preferably: in S3, the specific steps of high temperature treatment are:
[0025] S31: Heating: directly heating the preheated mixture to 600°C and keeping it at that temperature for 1.5 hours; heating using a high temperature resistance furnace;
[0026] S32: Molten salt catalysis: The molten salt catalyst is controlled to be in a molten state, and the carbon structure in the graphite powder is efficiently cut through molten salt catalysis.
[0027] Preferably: in said S4, the specific steps of cooling and soaking are:
[0028] S41: Cooling: cooling the mixed material after high temperature treatment to room temperature;
[0029] S42: Soaking in deionized water: Place the cooled mixture in deionized water and soak for 30 minutes; stir with a magnetic stirrer to ensure full dispersion;
[0030] S43: Ultrasonic separation: Use an ultrasonic cleaning machine for ultrasonic separation for 1.2 hours with the parameters set to 120W, 45kHz; ensure that the suspension is evenly distributed.
[0031] Preferably: in S5, the specific steps of centrifugation and dialysis are:
[0032] S51: Centrifugation: The suspension was centrifuged at 11,000 rpm for 30 min;
[0033] S52: Initial collection: collect the supernatant and discard the precipitate;
[0034] S53: Dialysis: The centrifuged fluid was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 750 Daltons, with the water changed every 12 hours;
[0035] S54: Second centrifugation: The dialyzed fluid was centrifuged again at 11,000 rpm for 30 minutes;
[0036] S55: Secondary dialysis: The liquid after the secondary centrifugation was dialyzed for 1.8 days using a dialysis bag with a molecular weight cutoff of 850 Daltons, with the water replaced every 12 hours.
[0037] Preferably: in S6, the specific steps of drying and collecting are:
[0038] S61: Drying: The dialyzed product was vacuum dried at 70°C for 24 hours;
[0039] S62: collecting: collecting the dried graphene quantum dot finished product;
[0040] S63: Particle size detection: Use a dynamic light scattering instrument to measure the particle size distribution of graphene quantum dots to ensure that the average particle size is below 3 nanometers.
[0041] Preferably: in S7, the specific steps of surface treatment are:
[0042] S71: Polymer resin selection: Choose epoxy resin or polyvinyl alcohol as the surface treatment material;
[0043] S72: Dip coating: immerse the graphene quantum film in the polymer resin solution for 5 minutes to ensure uniform coating;
[0044] S73: Spraying: Use a spray gun to evenly spray the polymer resin on the surface of the graphene quantum film;
[0045] S74: Drying: Dry at 70°C for 12 hours to ensure complete curing;
[0046] S75: Quality inspection: Check the quality of the graphene quantum film to ensure there is no damage or bubbles.
[0047] Preferably: in said S8, the specific steps of the functionalization treatment are:
[0048] S81: Functional group selection: Select functional groups, including amino or carboxyl groups, and prepare amino or carboxyl solutions according to the selected functional groups;
[0049] S82: Soaking: immersing the graphene quantum film in an amino or carboxyl solution for 3 hours;
[0050] S83: Drying: Take out and dry at 65℃ for 18 hours to ensure complete drying;
[0051] S84: Performance test: Test the adsorption capacity or catalytic activity of the functionalized graphene quantum membrane.
[0052] A graphene quantum material is prepared according to the above-mentioned method for preparing the graphene quantum material.
[0053] The beneficial effects of the present invention are:
[0054] 1. The present invention realizes efficient cutting of carbon structure in graphite powder through molten salt catalysis and high temperature treatment steps, and effectively removes impurities through centrifugation and dialysis processes, ensuring the high purity of graphene quantum dots.
[0055] 2. The present invention adopts precisely controlled ultrasonic separation and centrifugation technology to ensure that the graphene quantum dots have a uniform size distribution and the average particle size is controlled below 3 nanometers, which is conducive to its application in the fields of electronics and optics.
[0056] 3. The graphene quantum film prepared by the present invention has the characteristics of high temperature resistance, acid and alkali resistance, IPX7 waterproof grade, etc. At the same time, it is non-toxic and harmless material, green and environmentally friendly, ensuring the safety and long-term stability of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1The present invention is a flow chart of a method for preparing a graphene quantum material. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.
[0059] Embodiment 1:
[0060] A method for preparing a graphene quantum material, comprising:
[0061] S1: Material collection: mechanically mix graphite powder blocks and molten salt catalyst in a mass ratio of 1:3-7 to obtain a mixture;
[0062] S2: Pretreatment: preheat the mixture of S1 at 320-480°C and keep it warm for 0.8-1.8 hours to remove impurities in the mixture;
[0063] S3: High temperature treatment: directly heat the preheated mixture to 580-680℃ and keep it warm for 1.2-2.2 hours;
[0064] S4: Cooling and soaking: After the mixture treated at high temperature is cooled to room temperature, it is treated with deionized water and ultrasonically separated for 1.2 hours to obtain a suspension;
[0065] S5: Centrifugation and dialysis: Centrifuge the suspension at 11,000 rpm for 25-35 minutes to remove the residual starting material; dialyze the centrifuged liquid for 1.5-2.5 days using a dialysis bag with a molecular weight cutoff of 600-900 Daltons, changing the water every 12 hours;
[0066] S6: Drying and collection: The dialyzed product is vacuum dried at 65-75°C for 18-26 hours to obtain a finished graphene quantum dot product;
[0067] S7: Surface treatment: The surface of the finished graphene quantum dot product is treated with a polymer resin; the polymer resin includes epoxy resin, polyvinyl alcohol, etc., and the treatment method includes dipping, spraying, etc.; the obtained graphene quantum film;
[0068] S8: Functionalization treatment: immerse the graphene quantum film in an amino or carboxyl solution for 2-4 hours; take it out and dry it at 60-70°C for 12-24 hours.
[0069] Among them, in said S1, the specific steps of taking materials are:
[0070] S11: Graphite powder block selection: Select industrial-grade graphite powder blocks, ensuring that the ash content is no more than 0.05%, the moisture content is no more than 0.02%, the carbon content is more than 99%, and the particle size is 800-12000 mesh;
[0071] S12: Preparation of molten salt catalyst: select cesium carbonate molten salt as a catalyst and mix them in a mass ratio of 1:4; put the cesium carbonate molten salt into a drying oven and preheat it to 100° C. to remove moisture;
[0072] S13: Mechanical mixing: Put the graphite powder block and the preheated cesium carbonate molten salt into a ball mill and mix them at a speed of 300 rpm for 2 hours.
[0073] Among them, in said S2, the specific steps of preprocessing are:
[0074] S21: Preheating treatment: preheat the mixture of S1 at 360°C and keep it warm for 1 hour; use a high temperature furnace for preheating;
[0075] S22: Impurity removal: Protect with inert gas (such as argon) to prevent oxidation; use a vacuum system to remove volatile impurities;
[0076] S23: Cooling: Cool naturally to room temperature and set aside.
[0077] Among them, in said S3, the specific steps of high temperature treatment are:
[0078] S31: Heating: directly heating the preheated mixture to 600°C and keeping it at that temperature for 1.5 hours; heating using a high temperature resistance furnace;
[0079] S32: Molten salt catalysis: The molten salt catalyst is controlled to be in a molten state, and the carbon structure in the graphite powder is efficiently cut through molten salt catalysis.
[0080] Wherein, in said S4, the specific steps of cooling and soaking are:
[0081] S41: Cooling: cooling the mixed material after high temperature treatment to room temperature;
[0082] S42: Soaking in deionized water: Place the cooled mixture in deionized water and soak for 30 minutes; stir with a magnetic stirrer to ensure full dispersion;
[0083] S43: Ultrasonic separation: Use an ultrasonic cleaning machine for ultrasonic separation for 1.2 hours with the parameters set to 120W, 45kHz; ensure that the suspension is evenly distributed.
[0084] Wherein, in said S5, the specific steps of centrifugation and dialysis are:
[0085] S51: Centrifugation: The suspension was centrifuged at 11,000 rpm for 30 min;
[0086] S52: Initial collection: collect the supernatant and discard the precipitate;
[0087] S53: Dialysis: The centrifuged fluid was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 750 Daltons, with the water changed every 12 hours;
[0088] S54: Second centrifugation: The dialyzed fluid was centrifuged again at 11,000 rpm for 30 minutes;
[0089] S55: Secondary dialysis: The liquid after the secondary centrifugation was dialyzed for 1.8 days using a dialysis bag with a molecular weight cutoff of 850 Daltons, with the water replaced every 12 hours.
[0090] Wherein, in said S6, the specific steps of drying and collecting are:
[0091] S61: Drying: The dialyzed product was vacuum dried at 70°C for 24 hours;
[0092] S62: collecting: collecting the dried graphene quantum dot finished product;
[0093] S63: Particle size detection: Use a dynamic light scattering instrument to measure the particle size distribution of graphene quantum dots to ensure that the average particle size is below 3 nanometers.
[0094] Wherein, in said S7, the specific steps of surface treatment are:
[0095] S71: Polymer resin selection: Choose epoxy resin or polyvinyl alcohol as the surface treatment material;
[0096] S72: Dip coating: immerse the graphene quantum film in the polymer resin solution for 5 minutes to ensure uniform coating;
[0097] S73: Spraying: Use a spray gun to evenly spray the polymer resin on the surface of the graphene quantum film;
[0098] S74: Drying: Dry at 70°C for 12 hours to ensure complete curing;
[0099] S75: Quality inspection: Check the quality of the graphene quantum film to ensure there is no damage or bubbles.
[0100] Among them, in said S8, the specific steps of functionalization treatment are:
[0101] S81: Functional group selection: Select functional groups, including amino or carboxyl groups, and prepare amino or carboxyl solutions according to the selected functional groups;
[0102] S82: Soaking: immersing the graphene quantum film in an amino or carboxyl solution for 3 hours;
[0103] S83: Drying: Take out and dry at 65℃ for 18 hours to ensure complete drying;
[0104] S84: Performance test: Test the adsorption capacity or catalytic activity of the functionalized graphene quantum membrane.
[0105] Embodiment 2:
[0106] A graphene quantum material is prepared by the preparation method of embodiment 1.
[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing graphene quantum material, characterized in that: The steps include: S1: Material collection: mechanically mix graphite powder blocks and molten salt catalyst in a mass ratio of 1:3-7 to obtain a mixture; S2: Pretreatment: preheat the mixture of S1 at 320-480°C and keep it warm for 0.8-1.8 hours to remove impurities in the mixture; S3: High temperature treatment: directly heat the preheated mixture to 580-680℃ and keep it warm for 1.2-2.2 hours; S4: Cooling and soaking: After the mixture treated at high temperature is cooled to room temperature, it is treated with deionized water and ultrasonically separated for 1.2 hours to obtain a suspension; S5: Centrifugation and dialysis: Centrifuge the suspension at 11,000 rpm for 25-35 minutes to remove the residual starting material; dialyze the centrifuged liquid for 1.5-2.5 days using a dialysis bag with a molecular weight cutoff of 600-900 Daltons, changing the water every 12 hours; S6: Drying and collection: The dialyzed product is vacuum dried at 65-75°C for 18-26 hours to obtain a finished graphene quantum dot product; S7: Surface treatment: The surface of the finished graphene quantum dot product is treated with a polymer resin; the polymer resin uses epoxy resin and polyvinyl alcohol, and the treatment method includes dipping and spraying to obtain a graphene quantum film; S8: Functionalization treatment: immerse the graphene quantum film in an amino or carboxyl solution for 2-4 hours; take it out and dry it at 60-70°C for 12-24 hours.
2. The method for preparing a graphene quantum material according to claim 1, characterized in that: In S1, the specific steps of taking materials are: S11: Graphite powder block selection: Select industrial-grade graphite powder blocks, ensuring that the ash content is no more than 0.05%, the moisture content is no more than 0.02%, the carbon content is more than 99%, and the particle size is 800-12000 mesh; S12: Preparation of molten salt catalyst: select cesium carbonate molten salt as a catalyst and mix them in a mass ratio of 1:4; put the cesium carbonate molten salt into a drying oven and preheat it to 100° C. to remove moisture; S13: Mechanical mixing: Put the graphite powder block and the preheated cesium carbonate molten salt into a ball mill and mix them at a speed of 300 rpm for 2 hours.
3. The method for preparing a graphene quantum material according to claim 2, characterized in that: In S2, the specific steps of preprocessing are: S21: Preheating treatment: preheat the mixture of S1 at 360°C and keep it warm for 1 hour; use a high temperature furnace for preheating; S22: Impurity removal: Protected by inert gas to prevent oxidation; use a vacuum system to remove volatile impurities; S23: Cooling: Cool naturally to room temperature and set aside.
4. The method for preparing a graphene quantum material according to claim 3, characterized in that: In S3, the specific steps of high temperature treatment are: S31: Heating: directly heating the preheated mixture to 600°C and keeping it at that temperature for 1.5 hours; heating using a high temperature resistance furnace; S32: Molten salt catalysis: The molten salt catalyst is controlled to be in a molten state, and the carbon structure in the graphite powder is efficiently cut through molten salt catalysis.
5. The method for preparing a graphene quantum material according to claim 4, characterized in that: In S4, the specific steps of cooling and soaking are: S41: Cooling: cooling the mixed material after high temperature treatment to room temperature; S42: Soaking in deionized water: Place the cooled mixture in deionized water and soak for 30 minutes; stir with a magnetic stirrer to ensure full dispersion; S43: Ultrasonic separation: Use an ultrasonic cleaning machine for ultrasonic separation for 1.2 hours with the parameters set to 120W, 45kHz; ensure that the suspension is evenly distributed.
6. The method for preparing a graphene quantum material according to claim 5, characterized in that: In S5, the specific steps of centrifugation and dialysis are: S51: Centrifugation: The suspension was centrifuged at 11,000 rpm for 30 min; S52: Initial collection: collect the supernatant and discard the precipitate; S53: Dialysis: The centrifuged fluid was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 750 Daltons, with the water changed every 12 hours; S54: Second centrifugation: The dialyzed fluid was centrifuged again at 11,000 rpm for 30 minutes; S55: Secondary dialysis: The liquid after the secondary centrifugation was dialyzed for 1.8 days using a dialysis bag with a molecular weight cutoff of 850 Daltons, with the water replaced every 12 hours.
7. The method for preparing a graphene quantum material according to claim 6, characterized in that: In S6, the specific steps of drying and collecting are: S61: Drying: The dialyzed product was vacuum dried at 70°C for 24 hours; S62: Collection: collecting the dried graphene quantum dot finished products; S63: Particle size detection: Use a dynamic light scattering instrument to measure the particle size distribution of graphene quantum dots to ensure that the average particle size is below 3 nanometers.
8. The method for preparing a graphene quantum material according to claim 7, characterized in that: In S7, the specific steps of surface treatment are: S71: Polymer resin selection: Choose epoxy resin or polyvinyl alcohol as the surface treatment material; S72: Dip coating: immerse the graphene quantum film in the polymer resin solution for 5 minutes to ensure uniform coating; S73: Spraying: Use a spray gun to evenly spray the polymer resin on the surface of the graphene quantum film; S74: Drying: Dry at 70℃ for 12 hours to ensure complete curing; S75: Quality inspection: Check the quality of the graphene quantum film to ensure there is no damage or bubbles.
9. The method for preparing a graphene quantum material according to claim 8, characterized in that: In said S8, the specific steps of functionalization treatment are: S81: Functional group selection: Select functional groups, including amino or carboxyl groups, and prepare amino or carboxyl solutions according to the selected functional groups; S82: Soaking: immersing the graphene quantum film in an amino or carboxyl solution for 3 hours; S83: Drying: Take out and dry at 65℃ for 18 hours to ensure complete drying; S84: Performance test: Test the adsorption capacity or catalytic activity of the functionalized graphene quantum membrane.
10. A graphene quantum material, characterized in that: The graphene quantum material is prepared according to the method for preparing the graphene quantum material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Technology and device for preparing graphene quantum material through ultra-short pulse laser induced cracking
CN115092913A